Call Me by My Name - Elliott, Sarah (Anti-Trafficking Review, 2018)
Response to the ATR Debate Proposition: ‘It is important and necessary to make clear distinctions between (irregular) migrants, refugees and trafficked persons.’ The image of rubber dinghies densely packed with people floating precariously in the Mediterranean Sea has become a symbol of our times. Among those in peril are persons who may have fled conflict, others who have left poverty and many who have suffered exploitation en route. Upon arrival, states are obliged to meet their immediate needs and to determine for what reasons they came, thereby identifying their rights under international and domestic law.